Risk factors and treatment outcomes of peristomal pyoderma gangrenosum in patients with inflammatory bowel disease. Issue 12 (7th May 2020) - Wang, Jingzhou; Prenner, Joshua; Wang, Wenfei; Sakuraba, Atsushi; Hyman, Neil; Dalal, Sushila; Hurst, Roger; Cohen, Russell D.; Umanskiy, Konstantin; Shogan, Benjamin D.; Alpert, Lindsay; Rubin, David T.; et al.
Summary: Background: Insufficient data exist for peristomal pyoderma gangrenosum (PPG), which primarily affects patients with inflammatory bowel disease (IBD). Aims: To evaluate the risk factors and treatment response of PPG in IBD patients in a real‐life cohort. Methods: Cases of PPG were identified retrospectively using ICD‐9/10 codes in patients with IBD who had an ostomy at a tertiary care centre. Disease‐specific characteristics were compared between groups with and without PPG, and response to therapy was evaluated in patients with PPG. Results: The cohort included 41 IBD patients with PPG and 123 IBD controls with an ostomy who never developed PPG. Patients with PPG were more likely to be female (76% vs 51%, P = 0.006), had higher BMIs (29.78 ± 0.89 vs 23.53 ± 0.51, P < 0.0001) and had increased usage of pouch belts (97% vs 71%, P = 0.0008) compared to controls. There were no differences in age at surgery (41.76 ± 2.60 vs 43.49 ± 1.50, P = 0.57) or IBD diagnosis (63% vs 54% Crohn's disease, P = 0.28) between PPG and controls. 85% of PPG patients achieved complete resolution with different treatments, including surgery. Complete resolution with topical corticosteroids and calcineurin inhibitors alone were low (14% and 13% respectively). Higher rates of complete resolution were reported with anti‐tumour necrosis factor (TNF) agents (63%) and surgical interventions (80%). Conclusions: Female gender, higher BMI and pouch belts were associated with increased risk of developing PPG. Most PPG cases resolved after treatment with the highest rates of complete resolution seen with anti‐TNF agents and surgical intervention.